Entre poder y resistencia. Tras los rastros de la política en Foucault - Nicolás del Valle Orellana (Revista Enfoques, 2012)
The aim of this essay is to analyze the concept of power in the “genealogical” moment of Foucault’s work in order to highlight some features of what the author understands by politics. The notion of power is outlined by means of a contrast with the traditional perspective in political thought in order to go into the categories used in his analytics of power. Finally, some notes on Foucault’s concept of politics are provided.